Ensuring safe and consistent coengineering of cyber‐physical production systems: A case study. Issue 9 (21st August 2020) - Tröls, Michael; Mashkoor, Atif; Demuth, Andreas; Egyed, Alexander
Abstract: In today's engineering projects, companies continuously have to adapt their systems to changing customers or dynamic market requirements. This requires a flexible, iterative development process in which different parts of the system under construction are built and updated concurrently. However, concurrent engineering becomes quite challenging in domains where different engineering artifacts from different disciplines come into play, such as safety‐critical cyber‐physical systems, where the involved engineering artifacts are quite heterogeneous in nature. In such systems, it is of utmost importance that different artifacts remain consistent in order to guarantee a correctly functioning end product. In this article, we discuss our experiences (with a leading company working in the areas of production automation and product processing) in maintaining the consistency between electrical models and the corresponding software controller, when both are subject to continuous changes. The article discusses how we let engineers describe the relationships between electrical models and the corresponding software controller code in the form of links and consistency rules. Additionally, we demonstrate that how our approach, through a process of continuous consistency checking, notifies engineers about the erroneous impact of their changes in various engineering artifacts.